Sugar accumulation may be regulated by a transcriptional cascade of ABA-VvGRIP55-VvMYB15-VvSWEET15 in grape berries under root restriction - Li, Dongmei (Plant science : an international journal of experimental plant biology, 2022)
Copyright © 2022. Published by Elsevier B.V.